Atmospheric chemistry of (CF3)2CCH2: OH radicals, Cl atoms and O3 rate coefficients, oxidation end-products and IR spectra. Issue 38 (15th September 2015) - Papadimitriou, Vassileios C.; Spitieri, Christina S.; Papagiannakopoulos, Panos; Cazaunau, Mathieu; Lendar, Maria; Daële, Véronique; Mellouki, Abdelwahid
Abstract : OH, Cl and O3 kinetics and IR spectra of (CF3 )2 CCH2 utilized to estimate tropospheric lifetimes, radiative efficiencies, global warming potentials, estimated photochemical ozone creation potentials and tropospheric oxidation end-products. Abstract : The rate coefficients for the gas phase reactions of OH radicals, k 1, Cl atoms, k 2, and O3, k 3, with 3, 3, 3-trifluoro-2(trifluoromethyl)-1-propene ((CF3 )2 CCH2, hexafluoroisobutylene, HFIB) were determined at room temperature and atmospheric pressure employing the relative rate method and using two atmospheric simulation chambers and a static photochemical reactor. OH and Cl rate coefficients obtained by both techniques were indistinguishable, within experimental precision, and the average values were k 1 = (7.82 ± 0.55) × 10 −13 cm 3 molecule −1 s −1 and k 2 = (3.45 ± 0.24) × 10 −11 cm 3 molecule −1 s −1, respectively. The quoted uncertainties are at 95% level of confidence and include the estimated systematic uncertainties. An upper limit for the O3 rate coefficient was determined to be k 3 < 9.0 × 10 −22 cm 3 molecule −1 s −1 . In global warming potential (GWP) calculations, radiative efficiency (RE) was determined from the measured IR absorption cross-sections and treating HFIB both as long (LLC) and short (SLC) lived compounds, including estimated lifetime dependent factors in the SLC case. The HFIB lifetime was estimated from kinetic measurements considering merely the OH reaction, τ OH = 14.8 days and including both OH and Cl chemistry, τ eff = 10.3 days. Therefore, GWP(HFIB, OH) and GWP(HFIB, eff) were estimated to be 4.1 (LLC) and 0.6 (SLC), as well as 2.8 (LLC) and 0.3 (SLC) for a hundred year time horizon. Moreover, the estimated photochemical ozone creation potential ( ε POCP ) of HFIB was calculated to be 4.60. Finally, HCHO and (CF3 )2 C(O) were identified as final oxidation products in both OH- and Cl-initiated oxidation, while HC(O)Cl was additionally observed in the Cl-initiated oxidation.